Mineral Composition Analysis of Red Horse-Chestnut (Aesculus × Carnea) Seeds and Hydroalcoholic Crude Extract Using ICP OES - Veronica D’Eusanio; Andrea Marchetti; Mirco Rivi; Lorenzo Morelli; Paolina Scarponi; Luca Forti; Lorenzo Tassi (Molecules)
This study presents findings on the metal and metalloid composition of red horse-chestnut (Aesculus × carnea, AXC) seeds, determined by the ICP OES technique. Samples were collected from five AXC plants located in Modena (Italy) over four consecutive years (2016–2019). The seeds underwent proximate analysis, which included measurements of moisture content, proteins, lipids, carbohydrates, ash, and elemental composition. The analysis revealed consistent values for these parameters throughout the study period. The metal content of the AXC seeds can be categorized into two groups: (i) major components, with concentrations ranging from 1 to <1500 mg/100 g dry basis (d.b.), where K was identified as the most abundant element, and (ii) minor constituents, with concentrations between 1 and <1000 μg/100 g d.b., with Li, Mo, and Ti at the lower concentration limit. Comparative analyses were performed using literature data on AHP and AHH seeds, which, like AXC, belong to the Sapindaceae family and were collected from the same area and period. A hydroalcoholic extract of AXC seeds was prepared annually and characterized, with results compared to a commercial product (AXC_herb). AXC extracts had approximately 30% higher analyte concentrations than AXC_herb, while AXC seeds showed 20–30% higher metal and metalloid levels than AHP and AHH.